2008
DOI: 10.1016/j.neulet.2007.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of sodium channel SCN3A in a patient with cryptogenic pediatric partial epilepsy

Abstract: Mutations in the sodium channel genes SCN1A and SCN2A have been identified in monogenic childhood epilepsies, but SCN3A has not previously been investigated as a candidate gene for epilepsy. We screened a consecutive cohort of 18 children with cryptogenic partial epilepsy that was classified as pharmacoresistant because of nonresponse to carbamazepine or oxcarbazepine, antiepileptic drugs that bind sodium channels. The novel coding variant SCN3A-K354Q was identified in one patient and was not present in 295 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 35 publications
1
120
0
2
Order By: Relevance
“…Although it is not known whether Nav1.1 and Nav1.3 channels produce resurgent currents, mutations that slow the rate of inactivation have been identified in these isoforms in patients with epilepsy (28,29), and it is therefore conceivable that resurgent currents could contribute to the pathophysiology of some inherited epilepsies. In our study, we showed that a mutation in the voltage-sensing segment 4 of the fourth domain, as well as mutations in the IFMT inactivation particle, induced enhanced resurgent currents, which suggests that any mutation that slows the rate of open channel fast inactivation might be able to induce resurgent currents.…”
Section: Figurementioning
confidence: 99%
“…Although it is not known whether Nav1.1 and Nav1.3 channels produce resurgent currents, mutations that slow the rate of inactivation have been identified in these isoforms in patients with epilepsy (28,29), and it is therefore conceivable that resurgent currents could contribute to the pathophysiology of some inherited epilepsies. In our study, we showed that a mutation in the voltage-sensing segment 4 of the fourth domain, as well as mutations in the IFMT inactivation particle, induced enhanced resurgent currents, which suggests that any mutation that slows the rate of open channel fast inactivation might be able to induce resurgent currents.…”
Section: Figurementioning
confidence: 99%
“…In the current study, we show that a common familial ALS mutant, hSOD1 A4V , shifts the voltage dependence and augments total Na + currents of the Na v channel, Na v 1.3, an isoform that is characteristic of embryonic motor neurons [17], which is documented to have a persistent inward sodium current and has been implicated in human neurological disease [20,21]. Our results suggest that changes in the biophysical properties of voltage-gated sodium channels are important in the genesis of mutant SOD1-induced hyperexcitability in ALS.…”
Section: Introductionmentioning
confidence: 62%
“…24 One mutation, K354Q, has been reported in Nav1.3 in a patient with cryptogenic epilepsy. 25 In addition, Estacion and colleagues demonstrated that K354Q mutation enhanced the Nav1.3 persistent current nearly twofold, and the ramp current more than twofold.…”
Section: Discussionmentioning
confidence: 99%